Enhancement of structural seismic performance of low-rise buildings using displacement-dependent tuned mass damper. (March 2022) - Lee, Bo-Han; Chen, Chun-Chung; Chen, Tsung-Wu; Shiao, Sheng-Yuan; Jiang, Chi-Rung; Yeh, Fang-Yao
Abstract: Tuned mass dampers are used to reduce vibrations of high-rise buildings due to wind disturbance. Specifically, the displacement-dependent tuned mass damper (DTMD) is an effective vibration energy absorber that is connected to a primary structure to reduce the vibration response of the structure under harmonic and external force disturbances. Its natural frequency is adjusted to be close to the fundamental vibration frequency of the primary structure; this leads to an antiphase resonance that dissipates the external force-induced disturbance energy. Several studies have proposed different optimization design objective functions and developed active and semi-active tuned mass damping systems to improve control efficiency significantly. Therefore, in this study, a reasonable mass and an objective function were considered using a simplified degree-of-freedom structural model (DTMD and primary structure) to derive an optimized design method and evaluate the feasibility of structural reinforcement through numerical analysis of the tuned mass damper and shaking table tests. The fundamental retrofit design process used in this study can facilitate the development of a specialized tuning mass damper that can be used in practical engineering applications, such as improving the seismic resistance of ancient and low-rise buildings.